Concrete road surface with the use of cement concrete - selected results. (2017) - Szymański, Paweł; Pikos, Michał; Nowotarski, Piotr
Abstract: The paper presents the technological concepts of the execution of modern concrete with the characteristics of road surface which have been subjected to comparative tests. Modified compositions of concrete mixtures with polymers have been tested that affect the mechanical properties and durability of the topcoat. Changes in strength properties of modified road concrete, also occurring under the influence of cyclic variable loads were investigated. Obtained results can be used to indicate the direction of further research leading to the most effective use of the advantages of polymer admixtures for concrete, mainly to improve economic indicators and reduce the negative impact of investments on the environment.